Perceptions of the appropriate response to norm violation in 57 societies - Eriksson, K.; Strimling, P.; Gelfand, M.; Junhui Wu; Abernathy, J.; Akotia, C. S.; Aldashev, A.; Andersson, P. A.; Andrighetto, G.; Anum, A.; Arikan, G.; Aycan, Z.; et al. (Nature Communications, 2021)
Norm enforcement may be important for resolving conflicts and promoting cooperation. However, little is known about how preferred responses to norm violations vary across cultures and across domains. In a preregistered study of 57 countries (using convenience samples of 22,863 students and non-students), we measured perceptions of the appropriateness of various responses to a violation of a cooperative norm and to atypical social behaviors. Our findings highlight both cultural universals and cultural variation. We find a universal negative relation between appropriateness ratings of norm violations and appropriateness ratings of responses in the form of confrontation, social ostracism and gossip. Moreover, we find the country variation in the appropriateness of sanctions to be consistent across different norm violations but not across different sanctions. Specifically, in those countries where use of physical confrontation and social ostracism is rated as less appropriate, gossip is rated as more appropriate.